Identifying acute myeloid leukemia subtypes based on pathway enrichment - Zhong, Ling; Luo, Jiangti; Dong, Junze; Yang, Xiang; Wang, Xiaosheng (Frontiers in Pharmacology, 2025)
Acute myeloid leukemia (AML) is the most common type of acute leukemia in adults and the second most common in children. Despite the introduction of targeted therapies, AML survival rates have shown limited improvement, particularly among older patients. This study explored personalized treatment strategies for AML by proposing a novel subtyping method. Through unsupervised clustering based on the enrichment scores of 14 pathways related to metabolism, immunity, DNA repair, and oncogenic signaling, we identified three AML subtypes: DNA repair (DR), immune-enriched (ImE), and immune-deprived (ImD), consistent in four independent datasets. DR is marked by high expression of DNA repair and metabolic pathways, high stemness and proliferation potential, as well as high sensitivity to chemotherapy. ImD is characterized by low expression of immune and oncogenic pathways, favorable survival prognosis, low mutation rates of RUNX1 and TP53, high homeostasis, and low migration potential. ImE exhibits high enrichment of immune and oncogenic pathways, low stemness and proliferation capacity, low homeostasis, high migration potential, and low sensitivity to chemotherapy. Our pathway enrichment-based subtyping approach would offer a promising framework for understanding the molecular heterogeneity of AML and guiding personalized treatment of this disease.